E-invoicing in Malaysia: invoice smarter - Nik Wil, Nor Jaslina; Che Hassan, Anita; Wan Hashim, Wan Murshida (Faculty of Accountancy, Universiti Teknologi MARA (UiTM) Cawangan Kelantan, 2024)
An e-Invoicing is a digital representation of a transaction between a supplier and a buyer, formatted in machine-readable manner. It is a file created in format specified by the IRBM. It is applicable to all taxpayers undertaking commercial activities in Malaysia in accordance with the phased mandatory implementation timeline (LHDNM, 2024). The adoption of e-Invoicing in Malaysia has been a noteworthy step to improve the effectiveness and transparency of the tax system. e-Invoicing, or electronic invoicing, will require the businesses to issue invoices electronically, streamlining processes and reducing dependency on hardcopy documentation (LHDNM, 2024). The Malaysian government has strategized to implement digital technologies in a variety of sectors, mainly in the financial and tax administration (Rashid, 2022). Thus, the implementation of e-Invoicing can be considered as one of the steps to digitalization and part of the government strategy. The adoption of the Goods and Services Tax (GST) in 2015 has spurred the interest for digital transformation in e-Invoicing implementation. The Malaysian government, through the Ministry of Finance and the Royal Malaysian Customs Department, has introduced several policies to encourage the adoption of e Invoicing (KPMG, 2020). In response to the abolishment of GST in 2018 and the re-introduction of the Sales and Service Tax (SST), the government still emphasized the importance of adopting e-Invoicing to increase compliance and decrease the tax gap (PwC, 2021).